Promoting outdoor recreation among older adults in Sweden - a theoretical and empirical foundation for the development of an intervention - Magnus Zingmark; Rosemarie Ankre; Sandra Wall-Reinius (BMC, 2021)
Abstract Background Disengagement from outdoor recreation may diminish the positive benefits on health and well-being in old age. The purpose of this study is to present a contextual, theoretical, and empirical rationale for an intervention, aiming to promote continued engagement in outdoor recreation for older adults in a Swedish context. Methods The paper includes a contextualization of outdoor recreation in Sweden, a presentation of evidence on health benefits related to engagement in outdoor recreation, together with theoretical frameworks that may guide future intervention designs. To add empirical knowledge, a mixed methods approach was applied, including an empirical data collection based on a quantitative survey (n = 266) and individual semi-structured interviews with older adults (n = 12). Survey data were presented with descriptive statistics. Associations between disengagement from previously performed activities and age and gender was analyzed with Chi2 tests. Transcripts and handwritten notes from the interviews were analyzed qualitatively to identify key themes, as well as patterns and disparities among respondents. Results Outdoor recreation was rated as important/very important by 90% of respondents of the survey. The interviews highlighted that engagement in outdoor recreation aided respondents to keep fit but had also relevance in terms of identity, experiences, and daily routines. Outdoor recreation close to the place of residence was most common and walking was the most frequently reported activity. While 80% considered their health to be good/very good, disability and long-term diseases were common and during the previous year, more than half of all respondents had disengaged from activities previously performed. Reasons for disengagement were mainly related to health decline or that activities were too demanding but also due to social loss. The interviews indicated that continued engagement was important but challenging, and that disengagement could be considered as a loss or accepted due to changing circumstances. Conclusions In the design of an intervention aiming to promote engagement in outdoor recreation for older adults, the following features are proposed to be considered: person-centeredness, promoting functioning, addressing self-ageism, providing environmental support, promoting subjective mobility needs and adaptation to find new ways to engage in outdoor recreation.